2010
DOI: 10.1128/aem.00563-10
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Avian Influenza Virus (H5N1) in Feathers Detached from Bodies of Infected Domestic Ducks

Abstract: Asian lineage highly pathogenic avian influenza virus (H5N1) continues to cause mortality in poultry and wild bird populations at a panzootic scale. However, little is known about its persistence in contaminated tissues derived from infected birds. We investigated avian influenza virus (H5N1) persistence in feathers detached from bodies of infected ducks to evaluate their potential risk for environmental contamination. Four-week-old domestic ducks were inoculated with different clades of avian influenza virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 55 publications
4
52
2
Order By: Relevance
“…between 2 and 5 days post inoculation, with the virus titres in feather samples being greater than or comparable with those in swabs at the majority of corresponding time points. In one infected duck, H5N1 HPAI-positive feathers were observed up to 8 days post inoculation, and viral antigen was detected immunohistochemically in the feather epidermal cells in the calamus (Yamamoto et al, 2008). High viral titres were also demonstrated in feathers collected from H5N1 HPAI-infected Pekin ducks, and infectivity of at least 10 4.3 median embryo infective dose/ml was shown to persist for at least 100 days in feather tissue stored at 48C (Yamamoto et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…between 2 and 5 days post inoculation, with the virus titres in feather samples being greater than or comparable with those in swabs at the majority of corresponding time points. In one infected duck, H5N1 HPAI-positive feathers were observed up to 8 days post inoculation, and viral antigen was detected immunohistochemically in the feather epidermal cells in the calamus (Yamamoto et al, 2008). High viral titres were also demonstrated in feathers collected from H5N1 HPAI-infected Pekin ducks, and infectivity of at least 10 4.3 median embryo infective dose/ml was shown to persist for at least 100 days in feather tissue stored at 48C (Yamamoto et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, feathers were collected from chickens and ducks at four H5N1 HPAIinfected locations when clinical signs were apparent, and in such disease scenarios the testing of feathers may be a highly practicable approach for HPAI RRT-PCR diagnosis. Yamamoto et al (2008) infected three Pekin ducks with a clade 2.2 H5N1 HPAI virus and observed no clinical signs other than corneal opacity. Presence of virus was demonstrated in feathers in all three ducks Table 3.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The result indicated that the transmission efficiency of HPAI H5N1 among poultry was 1.7 times higher in regions where infected wild birds had been detected compared with regions without infected wild birds (Keawcharoen et al, 2011). In addition, waterfowl may transfer the virus mechanically during long distance migration, and feathers infected with HPAI H5N1 could also be a source of environmental contamination with high viral loads (Uriarte et al, 2011;Yamamoto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%